2018
DOI: 10.1002/cam4.1641
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of association of OCT4 with LEF1 expression in esophageal squamous cell carcinoma and their impact on epithelial‐mesenchymal transition, invasion, and migration

Abstract: Esophageal squamous cell carcinoma (ESCC) is a malignant disease with poor prognosis. Because of early metastasis prior to diagnosis and therapeutic resistance, ESCC has become one of the leading causes of cancer‐related death. Here, we investigated the clinicopathological significance of the association of octamer‐binding transcription factor 4 (OCT4) with lymphoid enhancer‐binding factor 1 (LEF1) expression and the potential molecular mechanism in the epithelial‐mesenchymal transition (EMT), invasion, and mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 26 publications
(25 reference statements)
1
15
0
Order By: Relevance
“…Although we presented several positive aspects of genome editing to lead LEF1 expression in hUCB-MSCs, there are also several studies regarding the aberration of LEF1 gene expression in various cases of tumorigenesis and cancer cell proliferation, migration, and invasion. 43,44 Particularly, LEF1 expression has been reported in cancer cell types, such as some leukemias, lymphoma, squamous cell carcinoma, and colorectal cancer. 45,46 Lack of teratoma formation has been known in MSCs; however, the tumorigenic effect of LEF1 in hUCB-MSCs needs be tested in regard to long-term expression and survival.…”
Section: Discussionmentioning
confidence: 99%
“…Although we presented several positive aspects of genome editing to lead LEF1 expression in hUCB-MSCs, there are also several studies regarding the aberration of LEF1 gene expression in various cases of tumorigenesis and cancer cell proliferation, migration, and invasion. 43,44 Particularly, LEF1 expression has been reported in cancer cell types, such as some leukemias, lymphoma, squamous cell carcinoma, and colorectal cancer. 45,46 Lack of teratoma formation has been known in MSCs; however, the tumorigenic effect of LEF1 in hUCB-MSCs needs be tested in regard to long-term expression and survival.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the target genes of TFs such as LEF1 and TEAD4 were found to be differentially expressed in ESCC samples. Based on the ORA and GSEA, we found that the upregulated genes were significantly enriched in the components of the oncogenic pathways and the target genes of LEF1 and TEAD4, respectively, suggesting that the WNT, NOTCH, cell cycle, and Hippo signaling pathways were abnormally activated by their corresponding driver genes [ 26 , 27 ]. These oncogenic signaling pathways have been recurrently reported to lead to uncontrolled proliferation of cancer cells and unfavorable prognostic outcomes in several cancer types [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…International Publisher transition (EMT) of ESCC cells [7,8]. More recently, we found LEF1 could promote the stem-like phenotype and the tumorigenicity in ESCC [9].…”
Section: Ivyspringmentioning
confidence: 99%
“…Increasing studies have unveiled that dysregulation of LEF1 is implicated in the progression of multiple cancers, such as breast cancer, colon cancer, prostate cancer, et al 4 - 6 . Our previous studies showed that LEF1 was highly expressed in ESCC tissues and it could promote proliferation, migration, invasion and epithelial-mesenchymal transition (EMT) of ESCC cells 7 , 8 . More recently, we found LEF1 could promote the stem-like phenotype and the tumorigenicity in ESCC 9 .…”
Section: Introductionmentioning
confidence: 99%